The effects of voluntary adolescent alcohol consumption on alcohol palatability - Wukitsch, Thomas J. (Kansas State University, 2019)
The relationship between age, alcohol intake, and the hedonic value of alcohol is key to understanding the motivation to consume alcohol. It is uncertain whether alcohol drinking during adolescence changes alcohol’s hedonic value as measured by taste reactivity during adulthood. The current study compared voluntary ethanol (20% v/v) consumption among adolescent and adult Long-Evans rats in an intermittent access 2-bottle choice (IAE) paradigm and analyzed the effects of IAE on taste reactivity in adulthood compared to alcohol-naïve controls (CTRL). Blood ethanol was determined after a 28-min access period. For taste reactivity, orally infused fluids included water, ethanol (5, 20, & 40% v/v), and sucrose (0.01, 0.1, 1 M). IAE results indicate that adolescents drank more alcohol during IAE but had a lower rate of change in alcohol consumption across time compared to adults due to initially high adolescent drinking. During taste reactivity testing for ethanol, IAE rats had greater hedonic responding, less aversive responding, and a more positive relationship between hedonic responses and ethanol concentration than CTRL rats. Hedonic responses had positive while aversive responses had negative relationships with ethanol concentration and Total Ethanol Consumed during IAE. Adolescent+IAE rats displayed less hedonic and more aversive responses to ethanol than Adult+IAE rats. The adolescent group displayed less hedonic responding to sucrose than the adult group, but adolescent hedonic responding increased more steeply across sucrose concentrations. Hedonic responding for sucrose was unrelated to ethanol consumption. While many rats did not drink excessively, these results suggest alcohol consumption influences the future hedonic and aversive value of alcohol in a way that makes alcohol more palatable with greater prior consumption. However, it appears that those drinking alcohol as adolescents may be more resistant to this palatability shift than those first drinking as adults, suggesting different mechanisms of vulnerability to consumption escalation for adolescents and adults.
Keywords: Alcohol; Adolescent; Taste reactivity; Intermittent access to ethanol